AN EFFORTS TO PREVENT TERRORISM AS A TRANSNATIONAL CRIME THROUGH THE IMPLEMENTATION OF IMMIGRATION CONTROL - Atsil Syah Gibran; Ully Hidayati (Journal of Law and Border Protection, 2023)
The threat of terrorism in the world is increasing and the changes in tactics and strategies used by terrorist groups show the importance of international cooperation in fighting terrorism. Indonesia as a country with a strategic geographical location and abundant natural resources also faces the threat of terrorism. Movements of radical organizations such as ISIS, Al-Qaeda, and Jemaah Islamiyah have made Indonesia one of the targets for the spread of radicalism within the country. Therefore, supervision carried out by the immigration authorities plays an important role in controlling the potential for radicalism and terrorism. The Indonesian government has an obligation to protect sovereignty and maintain national integrity from threats both from within and from outside. Immigration as part of the government has a role in maintaining domestic security stability. In the context of immigration, strict monitoring of the movement of foreigners is very important in dealing with the threat of terrorism.